A study of oxygen gas sensing in Zn-doped SnO2 nanostructures. (5th June 2017) - Gupta, Parul; Sharma, S K
Abstract: Sol–gel synthesis of pure and Zn-doped SnO2 is demonstrated with variable concentration of Zn (1.5 wt%, 3 wt% and 4.5 wt%) for their potential oxygen sensing applications. X-ray diffraction measurements confirmed the tetragonal rutile type crystal structure of SnO2 nanoparticles having particle sizes as 14  ±  1 nm, 12  ±  1 nm, 10  ±  1 nm and 9  ±  1 nm for the pure, 1.5 wt% Zn, 3 wt% Zn and 4.5 wt% Zn-doped SnO2, respectively. The optical spectroscopy suggested an increase in the band-gap and oxygen deficiency with increase in Zn-doping in SnO2 . The I – V measurements yielded a high electrical resistance for 1.5 wt% Zn-doped SnO2 as compared to other specimens. The gas sensing measurements revealed an enhanced sensitivity (37.6%) in 1.5 wt% Zn-doped SnO2 for oxygen gas concentration in the range 5%–20% at 250 °C operating temperature in N2 atmosphere (0.4  ±  0.03 mbar) along with reduced response time as compared to pure, 3 wt% Zn and 4.5 wt% Zn-doped SnO2 .